2020
DOI: 10.1097/ta.0000000000003001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction following traumatic pelvic fracture

Abstract: BACKGROUND While sexual dysfunction (SD) in men following traumatic pelvic fracture is common, little is known of how men experience changes in their sexual health after injury. The aims of the present study were to explore the personal and interpersonal impacts of SD in men after pelvic injury and to understood how interactions with the health care system can be optimized to improve patient-centered trauma survivorship care. METHODS Fifteen semistructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Prior work using the same cohort of pelvic trauma patients has shown that spontaneous return of normal sexual function more than 1 year after injury was highly unlikely and that the negative impact of a failure to address sexual health concerns in this population cannot be understated. 13,18 These findings are similar to what has been reported in men following radical prostatectomy for prostate cancer. 26 However, while there has been tremendous interest in prostate cancer survivorship with numerous prior studies prospectively examining HrQOL and ED, these efforts have been lacking in the pelvic trauma literature.…”
Section: Discussionsupporting
confidence: 86%
“…Prior work using the same cohort of pelvic trauma patients has shown that spontaneous return of normal sexual function more than 1 year after injury was highly unlikely and that the negative impact of a failure to address sexual health concerns in this population cannot be understated. 13,18 These findings are similar to what has been reported in men following radical prostatectomy for prostate cancer. 26 However, while there has been tremendous interest in prostate cancer survivorship with numerous prior studies prospectively examining HrQOL and ED, these efforts have been lacking in the pelvic trauma literature.…”
Section: Discussionsupporting
confidence: 86%
“…Provider discomfort can deter patients from sharing their concerns, thwarting the possibility of productive interactions. Similarly, in a qualitative study investigating how men navigate conversations regarding sexual health after pelvic fracture, patients felt that physicians did not want to address sexual health, ignoring or passing over raised concerns 10 …”
Section: Discussionmentioning
confidence: 99%
“…The effects of sexual dysfunction on quality of life have been well‐studied, but there are few studies that discuss the treatment patterns and utilization of healthcare services following injury. Those that do exist pertain almost exclusively to men 8–10 . As such, how women experience sexual dysfunction after traumatic injury and how they navigate the healthcare system is currently not well‐documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Traumatic fractures are fractures caused by various exogenous traumatic events. They are characterized by suddenness and unpredictability (Johnsen et al, 2021;(Li et al, 2021b). They not only cause physical and cognitive damage to the individual, but also have an impact on their psychology, causing strong stress response, but when encountering frustration and adversity, not all individuals will have psychological problems or stress disorders, and some people will adapt well after stress (Xiao et al, 2020).
…”
mentioning
confidence: 99%